PENGARUH LABEL HALAL PADA PERTUMBUHAN KOSMETIK DAN PANDANGAN WANITA MUSLIM NEGARA ISLAM DUNIA - Dinar Haidayatullah (Universitas Trunojoyo Madura, 2018)
ABSTRACTEven though the concept of halal is not a major concern among both Muslim and non-Muslim consumers living in an Islamic country, they are concern about the underlying advantages that come with halal products. Nowadays, Muslim consumers are faced with a broad selection of cosmetic products and services that offer multiple choices with different brands either locally or internationally. Halal cosmetic products are not only suitable for Muslim consumers, but also to non Muslims because of the nature of the products in terms of its ingredients and the methods used to produce these products. Thus this conceptual paper will explore the underlying determinants that are likely to influence non-Muslim and Muslim consumers’ perceptions and attitudes towards halal cosmetic products in Islamic country. Recommendations for future research are also discussed.